2017
DOI: 10.1590/2317-1545v39n3174582
|View full text |Cite
|
Sign up to set email alerts
|

Computerized image analysis of seedlings to evaluate broccoli seed vigor

Abstract: -The computerized image analysis of seedlings constitutes an efficient technique to evaluate the quality of seed lots, since it is quick in responding, has a simple execution and reproduction. The goal of this research was to verify the efficiency of the computer image analysis of seedlings to detect vigor differences among broccoli seed lots and compare them with other traditionally used vigor tests. Computerized image analysis were performed by the Seed Vigor Imaging System (SVIS ® ), using 3-day-old seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In a similar manner, Corrêa et al (2019) concluded that the Seed Vigor Imaging System (SVIS®) constitutes a technique for evaluating cotton seed vigor, as there was correlation with other tests traditionally used with the same objective. Speed in obtaining results is an important aspect of the use of computerized image analysis of seedlings (Abud et al, 2017). Medeiros et al (2019) studied the physiological quality of common bean seeds with the Vigor-S® system and detected that the use of this image analysis technique allows evaluation of seed physiological potential, which shows the possibility of taking better advantage of the results obtained in the same evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar manner, Corrêa et al (2019) concluded that the Seed Vigor Imaging System (SVIS®) constitutes a technique for evaluating cotton seed vigor, as there was correlation with other tests traditionally used with the same objective. Speed in obtaining results is an important aspect of the use of computerized image analysis of seedlings (Abud et al, 2017). Medeiros et al (2019) studied the physiological quality of common bean seeds with the Vigor-S® system and detected that the use of this image analysis technique allows evaluation of seed physiological potential, which shows the possibility of taking better advantage of the results obtained in the same evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to consider the benefits of image analysis for phenotyping in breeding programs. This tool has been used for species distinction (Marques et al, 2019) and for seed vigor studies (Abud et al, 2017). For maize, computerized analysis has also been used for seed vigor determination (Medeiros et al, 2018), highlighting the potential applications of this tool in phenotyping and reducing the time and costs of program procedures by decreasing the probability of human error, among other advantages.…”
Section: Resultsmentioning
confidence: 99%
“…The uniformity index has great importance in the analysis of seed vigor, as a rapid and uniform emergence represents an adequate stand of seedlings in the field (Abud et al, 2017). However, this index should not be analyzed in isolation to generate information regarding seed vigor because lots composed only of poorly developed seedlings can also generate a high uniformity index.…”
Section: Resultsmentioning
confidence: 99%